Artificial intelligence in conceptual prototyping design - Volichenko, Olga; Tsurik, Tatiana (project baikal, 2024)
The treasures of world architecture, reflecting theories and concepts, principles and techniques of design, are an inexhaustible base for the growth and development of young architects, searching for ideas to create the image and form of an object. Artificial intelligence, in addition to developing floor plans, structural layouts, patterns for environmental and organisational decisions, etc., can effectively generate conceptual and prototypical images using the diffusion method. Artificial intelligence can significantly reduce the time of the creative process by offering a wide range of options for creative and practical solutions based on the prototype patterns and their descriptions offered to it.
Keywords: prototype design; artificial intelligence; innovation; creative process; artificial intelligence training